Faktor-Faktor yang Memengaruhi Kesehatan Reproduksi Remaja - Rahmawati, Siti; Setyowati, S.; Budiati, Tri; Rachmawati, Imami Nur (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to review publications or literature about the factors that affect adolescent reproductive health. The method used is Prisma (Preferred Reporting Items for Systematic Reviews and Meta-Analyses). The database that the author uses is Sciencedirect, Proquest, Scopus, Sage Journals, and Fifteen Total Articles conducted by the analysis. The results showed that communication factors with parents influenced adolescent reproductive health, the level of teenage education, knowledge, the environment of residence, early sex with many couples without using contraception, the influence of peers, exposure to information media, reproductive health services, economic status, and Attitudes, adolescents towards reproductive health. Conclusions: adolescent reproductive health is influenced by various factors from themselves, others, the environment of residence, or health care facilities. Keywords: Reproductive Health, Teenagers